Synthesizing Nile crocodile Crocodylus niloticus attack data and historical context to inform mitigation efforts in South Africa and eSwatini (Swaziland). Issue 5 (11th September 2020) - Pooley, Simon; Botha, Hannes; Combrink, Xander; Powell, George
Abstract: Conflicts with wildlife are a major challenge for conservation across Africa, and Nile crocodiles Crocodylus niloticus are allegedly responsible for more attacks on people than any other species; however, there is a lack of data regarding such attacks. We analysed reported attacks on people by Nile crocodiles in South Africa and eSwatini (Swaziland) during 1949–2016, identifying spatial and temporal patterns in attack incidence, as well as victim demographics. Through a literature review and archival searches we identified records of 214 attacks. Most attacks occurred in natural water bodies, with attacks in dams increasing since 2000. Most victims were attacked while swimming or bathing, others while fishing, doing domestic chores, and crossing waterways. There was a significant relationship between gender and activity when attacked. Children (< 16 years old) accounted for 51% of all attacks, with a higher fatality rate compared to adults. Most victims were male (65%), with teenage boys being the largest individual category. We make recommendations for conservation policy and management to mitigate attacks by Nile crocodiles.